(untitled) (American Journal of Islam and Society, 1989)
Introduction The employment of resources is important for any aspect of the spectrum of overall development, be it economic or non-economic, spiritual or material. Although spiritual matters seem to be noneconomic in nature, their inculcation and development involve the use of resources. Hence, Allah (SWT) instructs mankind to invest in the development of spiritual values. The spread and establishment of Islam require travelling, dissemination of knowledge, education, publication of literatw u, se of media, protecton of Islamic societies from non-Islamic forces (i.e. internal and external defense), administration of institutions intended for the implementation of Islamic obligations and norms, and the like. Each of these functions requires tremendous amounts of material and human resources. Economic development comprises two essential components: economic growth and equity in the distribution of income and wealth. Economic growth requires investable resources for producing capital goods, hiring workers and managers, acquiring raw materials, improving technology, and organizing the production process. In particular, capital formation and technological change have been considered as key factors in economic development; the availability of adequate investable resources is a prerequisite for the smooth supply and use of these factors. The Islamic code of life provides enormous incentives for mobilizing resources, both material and human, and an institutional framework conducive to efficient use of resources for development. This paper, which concentrates on mobilizing resources for development, discusses natural, human and financial resources, as well as the role of government and internal and external institutions in the development process ...